Legal Transplant: Influence of the Western Legal System in the Muslim Countries - Sri Wahyuni (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2022)
This article discusses the influence of Western legal systems on Islamic law in Muslim countries, such as Turkey, Egypt, Iraq, Kuwait, Syria, Libya, Pakistan, Indonesia, and Malaysia. It uses the comparative law scholars’ legal transplant theory to see the influence. The article may enrich the discourses in Comparative and History of Law. It may contribute to many scholars and reformers of law who choose the best model of Islamic law reforms according to the histories of the law of their countries. This study shows that the transplantation of Western law in Muslim countries has occurred since the colonialism period, World War I, and World War II. These legal transplants occur by taking part in a foreign legal system, namely the modern Western legal system, for overall such as in Turkey, as well as the majority of modern Western legal methods synthesized with local law, such as in Egypt, Indonesia, Malaysia, and other Muslim countries. There are three types of Muslim countries based on Islamic law reforms undertaken. They are the Muslim countries that apply Islamic law and traditional fiqh, with no legal transplant; the Muslim countries that adopt Western law. This is a legal transplant, and Muslim countries implement Islamic law using appropriate Western methods and procedures. Moreover, this is a partial legal transplant. The law reform in Muslim countries was carried out by intra- and extra-doctrinal reform, legislation (regulation), and codification methods. The last three methods are the partial legal transplant models.